Insulated box and refrigerated equipment with PCM for food preservation: State of the art. (March 2022) - Leungtongkum, Tanathep; Flick, Denis; Hoang, Hong Minh; Steven, Duret; Delahaye, Anthony; Laguerre, Onrawee
Abstract: The use of Phase Change Material (PCM) as a cold accumulator in refrigeration contexts leads to better food safety, food security and energy management. However, applying PCM in real usage still depends on the user's experience or a trial-and-error basis. Studies carried out on insulated boxes and in refrigerated equipment (refrigerated trucks, cold storage facilities, display cabinets and domestic refrigerators) were reported. The influence of the studied conditions such as PCM melting point, position, mass of PCM and load, insulation material, external temperature on air/product temperatures and energy consumption was analyzed. Important parameters enabling the application of PCM in boxes and refrigerated equipment are the wall insulation and PCM configuration cited previously. Because of the complex interactions between these parameters, they need to be considered together with the usage conditions. The relationships between heat exchange and airflow inside the equipment should be further studied notably in function to the PCM position. Highlights: PCM enhances quality preservation and energy management in food cold chains. PCM efficiency is related to the insulation of the system and PCM configuration. Current studies have shown the most efficient design for specific conditions only. A numerical study may be useful for box design and use conditions.